PEMIKIRAN EKONOMI IBNU KHALDUN DAN PENGARUHNYA TERHADAP SISTEM EKONOMI MODERN - Muhammad Jazuli; Ullkhissyah Syarifah Sendy (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to examine Ibnu Khaldun's economic thought and its impact on the contemporary economic system. This study uses a literature review methodology with descriptive qualitative techniques. Data were obtained from the Muqaddimah, scientific journals, books, and relevant academic literature. Data analysis uses the Miles and Huberman framework, including data reduction, data presentation, and formulation of conclusions. The results of the study show that Ibnu Khaldun's economic thought is still relevant to the modern economic system, particularly in aspects of labor productivity, taxation, market mechanisms, income distribution, and sustainable economic development. The concepts of division of labor, fiscal policy, and social welfare proposed by Ibnu Khaldun are related to modern economic theory. This study concludes that Ibnu Khaldun's economic thought contributes to the development of a more just, stable, and welfare-oriented economic system through a contemporary Islamic economic approach.